PENGARUH KEBIJAKAN UTANG STRUKTUR MODAL DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN DAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAN SUB-SEKTOR FARMASI TBK YANG TERDAFTAR DI BEI PERIODE 2021-2024 - Oktaviani Resi; Lita Permata Sari; Randika Fandiyanto (Fakultas Ekonomi dan Bisnis, 2025)
The progress and competition of economic conditions in the business world are indeed experiencing very rapid growth. This causes a lot of competition to occur in the business world and business today. This competition must be faced by the company to maintain operational activities and improve the quality of company performance so that the company can compete and be able to manage the assets it has to achieve company goals. The purpose of this study is to analyze and test Debt Policy, Capital Structure, and Profitability on Dividend Policy and Financial Performance as Intervening Variables. Analysis and hypothesis testing in this study using the Structure Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 Application, show that debt policy has a negative but not significant effect on financial performance. Capital structure has a significant positive effect on financial performance. Profitability has a significant negative effect on financial performance. Debt policy has a negative but not significant effect on dividend policy. Capital structure has a significant negative effect on dividend policy. Profitability has a negative but not significant effect on dividend policy. Financial performance has a significant positive effect on dividend policy.